Pengembangan Tepung Tempe dan Bayam Hijau (Amaranthus Tricolor L) Sebagai Bahan Substitusi Pepaya Sandwich Biskuit untuk Snack Remaja Putri Anemia. - Ervin Syah Pehlepi; Theresia Puspita; I Komang Suwita (Politeknik Kesehatan Kemenkes Malang, 2022)
ABSTRACT ERVIN SYAH PEHLEPI, 2022. Development of Tempeh Flour and Green Spinach (Amaranthus Tricolor L) as a Substitute for Papaya Sandwich Biscuits for Snacks Adolescent Daughters with Anemia. Adviser: Theresia Puspita, STP, M.Si and I Komang Suwita, SST, MP. Anemia is a nutritional problem in Indonesia, the prevalence of anemia in Indonesia in 2013 was 37.1 percent and there was an increase in 2018 of 48.9 percent with the proportion of anemia of 84.6 percent in the 15 to 24 year age group. The increased risk of anemia in adolescent girls occurs because women experience menstruation and low dietary iron intake. This type of research is experimental using a completely randomized design (CRD) using 3 treatment levels and 3 replications so that the experimental unit becomes 9 units in substitution, namely wheat flour: tempeh flour: green spinach as ingredients for making papaya sandwich biscuits based on food. distraction in adolescent girls. This research was carried out in May-June 2022. The results of the study were 1) Tempe flour and green spinach (Amaranthus Tricolor L) as a substitute for papaya sandwich biscuits had an effect on chemical quality (moisture content and ash content). The highest water content was found in the P1 treatment of 9.7 percent. While the highest ash content was in the P1 treatment of 2.8 percent. 2) Tempe flour and green spinach (Amaranthus Tricolor L) as substitutes for papaya sandwich biscuits have an effect on nutrient levels (protein content, fat content, carbohydrate content). The highest protein content was found in the P3 treatment of 5.3g per 100g, the highest fat content in the P3 treatment of 2.6g per 100g and the highest carbohydrate content in the P1 treatment of 80.4g per 100g. 3) Tempe flour and green spinach (Amaranthus Tricolor L) as substitutes for papaya sandwich biscuits have an effect on organoleptic quality, namely taste. The most preferred taste in P1 treatment which has an average value of 3.36. 4) conclusion for the best formulation of tempeh flour and green spinach (Amaranthus Tricolor L) as a substitute for papaya sandwich biscuit, namely P1 treatment. Keywords: tempeh flour, green spinach (Amaranthus Tricolor L), papaya, sandwich biscuit, anemic teenage girls.